The clinical and pathological significance of tertiary lymphoid structure in extramammary Paget's disease - Xi, Ningyuan; Xu, Xiaoxiang; Xu, Mingyuan; Wu, Nanhui; Wu, Yuhao; Chen, Jiashe; Liu, Shuyi; Jiang, Long; Yan, Guorong; Zhang, Guolong; Liu, Yeqiang (Frontiers in Immunology, 2024)
BackgroundTumor-associated tertiary lymphoid structures (TLSs) are functional immune-responsive aggregates, which have been reported to be associated with better prognosis in various tumors. However, their exact characteristics and prognostic value in extramammary Paget’s disease (EMPD) remain unknown.ObjectiveTo explore the features of TLSs in EMPD and their association with clinicopathological characteristics.MethodsIn total, 171 EMPD patients from 2015 to 2023, retrospective, single center cohort were collected to assess the presence, maturation status, and location of TLSs by immunohistochemistry. Then, their clinicopathologic association and prognostic significance were further examined.ResultsTLSs were detected in 97 cases (57%) of 171 EMPD patients, including high-density TLSs in 88 cases (91%), peritumoral TLSs (pTLSs) in 89 cases (92%), TLSs around appendages (aTLSs) in 23 cases (24%), and mature TLSs in 16 cases (16%). Secondary EMPD was more likely to produce TLS (Secondary: 16/21 [76%]; Primary: 81/150 [54%]; P = 0.06), and more likely to produce Mature TLS (Secondary: 5/10 [50%]; Primary: 11/80 [14%]; P = 0.02). The subjective symptoms of EMPD patients did not seem to correlate with the presence of TLS. EMPD patients with tumor invasion were more likely to form mature TLS (Invasion: 8/32 [25%]; In situ: 8/65 [12%]; P = 0.06), recurrent EMPD patients were more likely to form TLS (Recurrent: 34/50 [68%]; Initial: 63/121 [52%]; P = 0.06) especially mature TLS (Recurrent: 8/34 [24%]; Initial: 8/63 [13%]; P = 0.04). The depth of tumor invasion in EMPD patients with mature TLS was mostly less than or equal to 4mm (mature TLS+: 7/8 [88%]; TLS-: 6/17 [35%]; P = 0.05), aTLS were less common in EMPD patients with skin appendage invasion (aTLS+: 4/23 [17%]; aTLS-: 32/74 [43%]; P = 0.03). The same EMPD patients relapse after, the existence of TLS increased [TLS+ (initial): 9/17 (53%); TLS+ (recurrence):14/17 (82%); P =.07].LimitationsRetrospective study design.ConclusionsMature TLS is a positive prognostic factor for invasive EMPD and may serve as a new biomarker and therapeutic target for EMPD.